Wind Stress‐Induced Multiyear Predictability of Annual Extratropical North Atlantic Sea Surface Temperature Anomalies - Reintges, Annika; Latif, Mojib; Bordbar, Mohammad Hadi; Park, Wonsun (Geophysical Research Letters, 2020)
Long‐term predictability of the North Atlantic sea surface temperature (SST) is commonly attributed to buoyancy‐forced changes of the Atlantic Meridional Overturning Circulation. Here we investigate the role of surface wind stress forcing in decadal hindcasts as another source of extratropical North Atlantic SST predictability. For this purpose, a global climate model is forced by reanalysis (ERA‐interim) wind stress anomalies over the period 1979–2017. The simulated climate states serve as initial conditions for decadal hindcasts. Significant skill in predicting detrended observed annual SST anomalies is observed over the extratropical central North Atlantic with anomaly correlation coefficients exceeding 0.6 at lead times of 4 to 7 yrs. The skill is insensitive to the calendar month of initialization and primarily linked to upper ocean heat content anomalies that lead anomalous SSTs by several years.